2022
DOI: 10.3390/cells11121914
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Carbonate Hydroxyapatite and Stem Cells from Human Deciduous Teeth Promotes Bone Regeneration by Enhancing BMP-2, VEGF and CD31 Expression in Immunodeficient Mice

Abstract: The objective of this study was to clarify the efficiency of a combination of stem cells from human deciduous teeth and carbonate apatite in bone regeneration of calvarial defects. Immunodeficient mice (n = 5 for each group/4 groups) with artificial calvarial bone defects (5 mm in diameter) were developed, and stem cells from human deciduous teeth (SHEDs) and carbonate hydroxyapatite (CAP) granules were transplanted with an atelocollagen sponge as a scaffold. A 3D analysis using microcomputed tomography, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Li et al (2022) reported that LIPUS could enhance the mRNA level and secretion of VEGF in endothelial cells. As a proangiogenic cytokine, VEGF-mediated signaling has been demonstrated to have crosstalk with BMP signal transduction, which plays a critical role in the biofunctions of stem cells in vivo (Grosso et al, 2017;Putranti et al, 2022). Zhang et al (2014) previously proved that the combined treatment with VEGF and BMP-2 could promote bone regeneration by facilitating endogenous stem cell homing and directing the differentiation of these cells into endothelial and osteogenic lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2022) reported that LIPUS could enhance the mRNA level and secretion of VEGF in endothelial cells. As a proangiogenic cytokine, VEGF-mediated signaling has been demonstrated to have crosstalk with BMP signal transduction, which plays a critical role in the biofunctions of stem cells in vivo (Grosso et al, 2017;Putranti et al, 2022). Zhang et al (2014) previously proved that the combined treatment with VEGF and BMP-2 could promote bone regeneration by facilitating endogenous stem cell homing and directing the differentiation of these cells into endothelial and osteogenic lineages.…”
Section: Discussionmentioning
confidence: 99%
“…(IIIb) After 8 weeks postimplantation, histological findings (Masson’s Trichrome) demonstrated higher bone regeneration (red, black arrows) in CSDs grafted with SHED/CAP scaffolds compared to acellular scaffolds. The figure is reprinted (adapted) with permission from reference under the CC BY-NC-ND license (). (IV) ADSCs-loaded β-TCP granules or bioglass were grafted into CSDs in patients, enhancing bone healing.…”
Section: Stem Cells As a Source Of Bioactive Molecules For Enhancing ...mentioning
confidence: 99%
“…SHEDs are derived from pulp tissue of deciduous teeth. When SHEDs were seeded on Col sponges containing carbonate apatite (CAp) and implanted into cranial CSDs in immunodeficient mice, they showed the most significant osteoinductive activity compared to Col sponges containing solely SHEDs or CAp, suggesting a synergistic effect of cells and CAp on osteogenesis (Figure III). A different investigation showed that growing SHEDs on scaffolds with osteogenic culture medium for a week in vitro before grafting into rat calvarial CSDs, enhanced bone regeneration .…”
Section: Stem Cells As a Source Of Bioactive Molecules For Enhancing ...mentioning
confidence: 99%
See 1 more Smart Citation
“…39 It has been reported that bone regeneration can be promoted and bone defects can be repaired by enhancing VEGF protein expression. 40 Although the role of VEGF in promoting tissue repair and fracture healing is well established, the importance and role of VEFF may vary at different stages of the bone healing process, for example, the results of a study suggesting that the formation of osteonecrosis is not due to VEGF-mediated failure of angiogenesis. 41 Among the VEGF family, VEGF-A has a leading role in angiogenesis.…”
Section: Introductionmentioning
confidence: 99%